Reforming Allied Authoritarian States: The Failure of United States Democracy Promotion in Egypt before the 'Arab Spring'. Issue 4 (2nd October 2022) - Pee, Robert
ABSTRACT: This article analyses the failure of American democracy promotion in Egypt before and during the 2011 Arab Spring, through a comparison with successful American support for democratic transitions in allied authoritarian regimes during the 1980s, executed through a combination of top-down diplomatic pressure and bottom-up democracy building by non-governmental organisations (NGOs). In Egypt, American policymakers misjudged the stability of the Mubarak regime and relaxed top-down pressure for liberalisation before the Arab Spring, while greater implementation of bottom-up democracy programs by United States government agencies resulted in the obstruction of these programs by the Mubarak regime and American policymakers. The case of Egypt illustrates the importance of American policymakers' perceptions of regime stability for the priority which Washington accords to democracy promotion in policy towards allied authoritarian regimes, and the impact of American government control of bottom-up democracy programs on democracy building in allied authoritarian states.